MODERN NON-INVASIVE METHODS OF ENDOMETRIOSIS DIAGNOSTICS: POSSIBILITIES AND PROSPECTS (International journal of medical sciences, 2026)
Endometriosis is a chronic estrogen-dependent disease characterized by the presence of endometriotic tissue outside the uterine cavity and accompanied by pain, reproductive dysfunction, and a reduced quality of life. Despite its significant prevalence among women of reproductive age, diagnosis remains challenging. Traditionally, laparoscopy with histological confirmation has been considered the "gold standard" for diagnosis verification. However, its invasive nature limits its use as a primary diagnostic method. Therefore, noninvasive methods for detecting endometriosis are particularly relevant. This article presents an analysis of modern instrumental, laboratory, and molecular diagnostic technologies, their information content, limitations, and prospects for their implementation in clinical practice.